Parsing the phenotype of obsessive-compulsive tic disorder (OCTD): a multidisciplinary consensus. (3rd April 2017) - Dell'Osso, Bernardo; Marazziti, Donatella; Albert, Umberto; Pallanti, Stefano; Gambini, Orsola; Tundo, Antonio; Zanaboni, Carlotta; Servello, Domenico; Rizzo, Renata; Scalone, Luciana; Benatti, Beatrice; Altamura, A. Carlo; et al.
Abstract: Obsessive-Compulsive Disorder (OCD) and Tic Disorder (TD) are highly disabling and often comorbid conditions. Of note, the DSM-5 acknowledged a new 'tic-related' specifier for OCD, which might be referred to as Obsessive-Compulsive Tic Disorder (OCTD), raising new interest toward a better clinical characterisation of affected patients. Available literature indicates that early onset, male gender, sensory phenomena and obsessions of symmetry, aggressiveness, hoarding, exactness and sounds as well as comorbidity with Attention Deficit Hyperactivity Disorder (ADHD) may be of more frequent observation in patients with OCTD. In order to share expertise in the field from different perspectives, a multidisciplinary panel of Italian clinicians, specifically involved in the clinical care of OCD and TD patients, participated into a consensus initiative, aimed to produce a shared document. As a result, after having examined the most relevant literature, authors sought to critically identify and discuss main epidemiologic, socio-demographic and clinical features characterising OCTD patients, along with other specific aspects including Health-Related Quality-of-Life (HRQoL), economic consequences related with the condition and its management, as well as treatment-related issues, that need to be further investigated.